Influence of interorganizational relationships on SMEs’ e-business adoption - Chong, Alain Yee Loong; Ooi, Keng Boon; Lin, Binshan; Tang, Shu Yi (Emerald Group Publishing Limited, 2009)
Purpose – The objective of this paper is to examine the influence of interorganizational relationships on the adoption of e-business in the supply chain of Malaysian small and medium enterprises (SMEs). Design/methodology/approach – A questionnaire was distributed to 200 Malaysian SMEs with a response rate of 68 percent. Data were analyzed by employing multiple regression analysis. Findings – Interorganizational relationships such as communication, collaboration and information sharing were found to be significant in affecting Malaysian SMEs’ decision to adopt e-business in their supply chain. Contrary to existing literatures, this research found that trust and trading partners’ power have no significant influence on the adoption of e-business in the supply chain of Malaysian SMEs. Practical implications – Organizations that would like to adopt e-business in their supply chain with their trading partners will be able to apply strategies based on the findings from this research. Based on these finding, organizations that would like to implement e-business with their trading partners in Malaysia should focus on improving interorganizational relationships such as communication, collaboration and information sharing. Originality/value – The findings created an understanding of what attributes of interorganizational relationships influence the adoption of e-business in the supply chain. In terms of theoretical contributions, this study has extended previous researches conducted in Western countries and provides great potential by advancing the understanding between the association of adoption factors and e-business adoption in Malaysian SMEs. SMEs planning to adopt e-business in their supply chain would be able to applied strategies based on the findings from this research.